Optimalisasi Pembibitan Terumbu Karang Teluk Pantai Wantopi Dengan Media Rangka Persegi Panjang Menggunakan Metode Transplantasi Tanam Tempel Untuk Mendukung Keberlanjutan Ekosistem Laut - Sarimuddin, Sarimuddin; Asdy, Muhamad; Yusri, Halmina; Alvia, Alvia; Rian, Ahmad; Aja, Aja; Ahmad Ghozali, Gus; Rusmala, Rusmala; Febriana, Febriana; Yasin, Abdul; Suryadin, Fitri; Nurmira, Nurmira; Fajrianti, Nur; Maada, Yayan; Amin, Ali; Fauzan, Irsyad (BALE LITERASI, 2025)
This Community Service Program aims to optimize coral reef nurseries in Wantopi Bay by utilizing rectangular frames using the transplantation method. This method is applied to improve the survival and growth of coral fragments attached directly to the frames as a nursery medium. The program implementation involved training and participation of local communities in the coral reef nursery and maintenance process. Results showed an increase in the survival rate of coral fragments and increased community awareness and active involvement in maintaining marine ecosystems. This approach has proven effective in supporting coral reef rehabilitation while strengthening the function of marine ecosystems as a habitat for biota, coastal protection, and a source of livelihood for coastal communities. This program is expected to become a model for sustainable coral reef nurseries and empower communities in marine conservation in Wantopi Bay.